AI-Driven Risk Management: Transforming Financial Decision-Making - Iswarya Konasani (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of artificial intelligence in financial risk management represents a transformative advancement in the industry, revolutionizing traditional approaches to credit scoring, underwriting, and risk assessment. This comprehensive article examines the implementation of AI-driven systems across financial institutions, highlighting significant improvements in operational efficiency, decision accuracy, and risk prediction capabilities. The article explores the evolution of machine learning models, advanced analytics, and automated systems that have enhanced portfolio management and regulatory compliance while enabling more inclusive financial services. Through detailed examination of technical implementations, challenges, and emerging technologies including quantum computing and natural language processing, this article demonstrates how AI-driven solutions are reshaping risk management practices and creating new possibilities for financial decision-making.
Keywords: Artificial Intelligence; Financial Risk Management; Machine Learning Models; Predictive Analytics; Risk Assessment Systems